Diaphragm for preventing short circuit in lithium ion battery and preparation method of diaphragm

By using the composite technology of foaming materials and polymer materials in the lithium-ion battery separator, the thermal runaway problem caused by internal short circuit is solved, and higher battery safety performance is achieved.

CN119495906APending Publication Date: 2025-02-21安徽得壹能源科技有限公司

Patent Information

Application Number
CN202411693391.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

When the existing lithium-ion battery separator is short-circuited, it cannot effectively prevent the puncture of lithium dendrites or metal foreign matters, resulting in the risk of thermal runaway.

Method used

The membrane made of foamed material and polymer material is made of a composite membrane. The volume of the foamed material expands rapidly when the temperature rises, separating the positive and negative electrodes, thereby stopping the internal short-circuit reaction.

Benefits of technology

It effectively prevents the occurrence of internal short circuits in lithium-ion batteries, eliminates the risk of thermal runaway, and improves the safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005151548560000011
    Figure HDA0005151548560000011
  • Figure HDA0005151548560000012
    Figure HDA0005151548560000012
  • Figure HDA0005151548560000021
    Figure HDA0005151548560000021
Patent Text Reader

Abstract

The invention provides a lithium ion battery internal short circuit prevention diaphragm and a preparation method thereof, the diaphragm comprises a foaming material and a polymeric membrane, and the foaming material is dispersed on the polymeric membrane. The diaphragm can ensure that once internal short circuit occurs in the lithium ion battery, local internal short circuit can cause heating and temperature rise of an internal short circuit area, and when the temperature reaches a certain temperature, the foaming material on the polymeric membrane is heated to rapidly expand, so that positive and negative electrodes in short circuit are separated, and the internal short circuit reaction is stopped; therefore, internal short circuit is avoided and further deterioration of the situation is prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium batteries, and in particular to a diaphragm for preventing internal short circuits in lithium ion batteries and a preparation method thereof. Background Art

[0002] With the booming development of electric vehicles in recent years, the demand for lithium-ion batteries has been increasing. However, as the capacity of lithium-ion batteries increases, their safety risks are also increasing exponentially. At present, since solid-state electrolytes have not yet been truly commercialized, polyolefin diaphragms are still the main type of diaphragms in lithium-ion batteries. However, since the puncture strength of polyolefin diaphragms is much lower than that of solid-state electrolytes, the risk of internal short circuits is relatively higher. A large number of thermal runaway analysis reports on lithium-ion batteries have pointed out that metal burrs penetrating the diaphragm and the overlap of positive and negative electrodes caused by the penetration of negative electrode lithium plating through the diaphragm are one of the important reasons for thermal runaway of lithium-ion batteries.

[0003] At present, the main methods for solving internal short circuit in industry are: strictly controlling the mixing of metal particles during the slurry preparation process, increasing the number of cleaning times and manual inspections; introducing a visual inspection system to check burrs during the pole roll slitting process, and adding manual microscopes to check burrs; coating ceramic particles on the surface of polyolefin diaphragms to increase the puncture resistance of the diaphragms, etc. However, there are some problems with the above methods: increasing the inspection frequency and inspectors will increase the production cost of lithium-ion batteries, and it is impossible to completely avoid the internal short circuit caused by lithium precipitation in the later stage of lithium-ion batteries; although coating ceramic particles on the surface of polyolefin diaphragms can improve the strength of the diaphragms to a certain extent, since the internal lithium-ion battery still relies on liquid electrolyte to conduct lithium ions, the diaphragm still has internal pores, which also provides a channel for the later growth of lithium dendrites, and still cannot avoid the occurrence of internal short circuits and the risk of thermal runaway. In the invention patent application with publication number CN113078414A, a composite diaphragm coated with polyethylene microspheres and ceramic coatings on one side of a polypropylene base film is provided. The diaphragm can achieve thermal closure at a relatively low temperature. When a lithium-ion battery experiences thermal runaway, the low-melting-point polyethylene microspheres melt under heat and fill the micropores of the polypropylene-based membrane, blocking the transmission of lithium ions and improving the safety performance of lithium-ion batteries. The mechanism of safety improvement is to achieve closure at a relatively low temperature through low-melting-point polyethylene microspheres. However, the closed pores of the polymer cannot cut off metal foreign matter or lithium dendrites, so further internal short circuits cannot be avoided. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one purpose of the present invention is a new diaphragm, which is made of a foamed material and a polymer material, so that once an internal short circuit occurs in a lithium-ion battery, the local internal short circuit will cause the internal short circuit area to heat up. When the temperature reaches a certain temperature, the foamed material on the polymer film expands rapidly due to heat, so that the positive and negative electrodes of the short circuit are separated, and the internal short circuit reaction stops, thereby preventing the internal short circuit from occurring and preventing the situation from further deteriorating.

[0005] In one aspect of the present invention, the present invention provides a diaphragm. According to an embodiment of the present invention, the diaphragm comprises a foaming material and a polymer film, wherein the foaming material is dispersed on the polymer film.

[0006] According to an embodiment of the present invention, the above-mentioned diaphragm may further include at least one of the following technical features:

[0007] According to an embodiment of the present invention, the foaming material is one or a mixture of azo organic matter, hydrazide organic matter, urea derivatives or azide compounds.

[0008] According to an embodiment of the present invention, the polymer material is one or a mixture of polyethylene, polypropylene, polyvinylidene fluoride, polyacrylic acid, polyacrylonitrile, polymethyl methacrylate, polyethylene oxide, polyimide, polyvinylidene fluoride-hexafluoropropylene, polyisophthalamide cellulose or chitosan.

[0009] In another aspect of the present invention, the present invention further provides a method for preparing a diaphragm. According to an embodiment of the present invention, the method comprises:

[0010] S1: performing a first mixing process on a foaming material, a polymer material and a solvent to obtain a first mixed liquid;

[0011] S2: adding a pore-forming agent to the first mixed solution for a second mixing treatment to obtain a second mixed solution;

[0012] S3: performing a casting process, an immersion process and a drying process on the second mixed liquid to obtain a diaphragm.

[0013] According to an embodiment of the present invention, the above method may further include at least one of the following additional technical features:

[0014] According to an embodiment of the present invention, the pore former is water and / or ethanol.

[0015] According to an embodiment of the present invention, the mass of the pore former is 0.5 wt.% to 5 wt.% of the mass of the first mixed solution.

[0016] According to an embodiment of the present invention, the pouring treatment and the immersion treatment are performed by pouring the second mixed liquid on the substrate to form a liquid film, and then immersing the substrate in water.

[0017] In another aspect of the present invention, the present invention further provides a method for preparing a diaphragm. According to an embodiment of the present invention, the method comprises:

[0018] A1: performing a first mixing process on a foaming material, a polymer material and a solvent to obtain a first mixed liquid;

[0019] A2: The first mixed solution is subjected to electrospinning and drying to obtain a separator.

[0020] According to an embodiment of the present invention, the above method may further include at least one of the following additional technical features:

[0021] According to an embodiment of the present invention, the electrospinning treatment is carried out by loading the first mixed liquid into an electrospinning syringe, the positive high voltage of the electrospinning treatment is 10 to 20 kV, the negative high voltage is 0 to 5 kV, the injection speed is 0.2 to 5 mL / h, the drum speed is 20-100 rpm, and the distance between the positive and negative electrodes is 10 to 20 cm.

[0022] According to an embodiment of the present invention, the foaming material is one or a mixture of azo organic matter, hydrazide organic matter, urea derivatives or azide compounds.

[0023] According to an embodiment of the present invention, the polymer material is one or a mixture of polyethylene, polypropylene, polyvinylidene fluoride, polyacrylic acid, polyacrylonitrile, polymethyl methacrylate, polyethylene oxide, polyimide, polyvinylidene fluoride-hexafluoropropylene, polyisophthalamide cellulose or chitosan.

[0024] According to an embodiment of the present invention, the solvent is one or a mixture of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, acetone, butanone, tetrahydrofuran, acetonitrile, and methanol.

[0025] According to an embodiment of the present invention, the mass fraction of the foaming material is 1wt.%-10wt.%, and the mass fraction of the polymer material is 90wt.%-99wt.%.

[0026] According to an embodiment of the present invention, the mass fraction of the foaming material and the polymer material in the first mixed liquid is 1 wt.% to 15 wt.%.

[0027] According to an embodiment of the present invention, the temperature of the drying process is 60-80°C.

[0028] According to an embodiment of the present invention, the high-safety diaphragm for a lithium-ion battery of the present invention is composed of a foaming material and a polymer film, wherein the foaming material is dispersed on the polymer film; when an internal short circuit occurs inside the battery, metallic foreign matter or lithium dendrites pierce the diaphragm, causing the temperature of the local area of ​​the internal short circuit to rise, and when the temperature reaches a certain temperature, the foaming material on the polymer film rapidly expands in volume due to the heat, so that the positive and negative electrodes of the short circuit are separated, and the internal short circuit reaction stops, thereby effectively preventing the occurrence of an internal short circuit in the lithium-ion battery.

[0029] According to an embodiment of the present invention, the present invention prepares a lithium-ion battery separator by compounding a foaming agent with a polymer through a casting method or an electrostatic spinning method, and the method is simple. When an internal short circuit occurs, the short-circuit point area will generate heat and heat up, thereby causing the foaming agent material in the separator to expand due to heat, and the positive and negative electrodes are separated in time, thereby preventing the battery from further deteriorating to thermal runaway. Compared with strengthening the control of foreign matter such as metal particles and burrs and improving the puncture strength of the separator, the use of this composite separator can more effectively prevent the occurrence of internal short circuits.

[0030] In another aspect of the present invention, the present invention further provides a diaphragm. According to an embodiment of the present invention, the diaphragm is prepared by the method described above.

[0031] In yet another aspect of the present invention, the present invention further provides a battery. According to an embodiment of the present invention, the battery comprises the above-mentioned separator. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0033] Figure 1 This is a SEM image of the casting method anti-internal short circuit composite diaphragm of Example 1;

[0034] Figure 2 This is a SEM image of the electrospinning method for preventing internal short circuit composite diaphragm of Example 2;

[0035] Figure 3 This is a schematic diagram of lithium dendrites or metal foreign matter piercing the diaphragm in Example 1;

[0036] Figure 4 This is a schematic diagram of the expansion of the foaming material after the lithium dendrite or metal foreign matter pierces the composite diaphragm in Example 1;

[0037] Figure 5 This is a schematic diagram of lithium dendrites or metal foreign matter piercing the diaphragm in Example 2;

[0038] Figure 6 This is a schematic diagram of the expansion of the foaming material after lithium dendrites or metal foreign matter pierces the composite diaphragm in Example 2. DETAILED DESCRIPTION

[0039] The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.

[0040] In the description of the present invention, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0041] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being "above", "above" or "above" a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being "below", "below" or "below" a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.

[0042] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0043] Embodiment 1

[0044] Weigh 9.5g of polyvinylidene fluoride powder and 0.5g of azobisisobutyronitrile powder, measure 55ml of N,N-dimethylformamide, add them to a beaker respectively, stir at 25℃ for 5h to obtain a uniform solution. Measure 0.65ml of deionized water and add it to the solution, continue to stir at 25℃ for 2h, and obtain a uniform solution again. Pour the solution into a glass container to form a liquid film, and then completely immerse it in deionized water. After 10min, a composite membrane is obtained. The composite membrane is dried at 60℃, and the final composite membrane is obtained after the water is completely dried.

[0045] Embodiment 2

[0046] Weigh 9.6g polyethylene powder and 0.4g p-toluenesulfonyl hydrazide powder, measure 30ml butanone and 60ml N, N-dimethylformamide, add them to a beaker respectively, stir at 25℃ for 8h to obtain a uniform solution. Take an appropriate amount of solution and add it to the electrospinning syringe, set the positive high voltage to 10kV, the negative high voltage to -1kV, the injection speed to 2ml / h, the roller speed to 20rpm, and the distance between the positive and negative electrodes to 10cm. Electrospin for 4 hours to obtain a nanofiber membrane. Place the diaphragm at 60℃ and dry for 12h to finally obtain a nanofiber composite membrane.

[0047] Comparative Example

[0048] The commercially available base membrane is polyethylene, and the commercial polyethylene separator is coated with a ceramic layer on one side.

[0049] The diaphragms of Example 1, Example 2 and the comparative example were used, and a positive electrode sheet made of NCM811 as the positive electrode material and a negative electrode sheet made of graphite as the negative electrode material were used. The N / P ratio was designed to be 1.12, and a 5Ah soft pack battery was assembled. The following experiment was conducted to simulate an internal short circuit: a 1C / 1C, 100% DOD cycle test was conducted at a low temperature of -20°C until the capacity reached 70% of the initial capacity or a safe runaway occurred. The capacity change, temperature change, and battery morphology change in this experiment were counted. The experimental results are shown in Table 1. To prevent the battery from being safely runaway, this experiment was conducted in an explosion-proof box.

[0050] Table 1

[0051] Capacity retention rate Maximum temperature Battery morphology after the experiment Embodiment 1 69.6%@17cycles 84.5℃ 21.6% expansion Embodiment 2 70.1%@15cycles 85.3℃ 18.2% expansion Comparative Example 75.0%@21cycles 347℃ Fire

[0052] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0053] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A diaphragm, characterized in that: The invention comprises a foaming material and a polymer film, wherein the foaming material is dispersed on the polymer film.

2. The diaphragm according to claim 1, characterized in that The foaming material is one or a mixture of azo organic matter, hydrazide organic matter, urea derivative or azide compound.

3. The diaphragm according to claim 1, characterized in that The polymer material is one or a mixture of polyethylene, polypropylene, polyvinylidene fluoride, polyacrylic acid, polyacrylonitrile, polymethyl methacrylate, polyethylene oxide, polyimide, polyvinylidene fluoride-hexafluoropropylene, polyisophthalamide cellulose or chitosan.

4. A method for preparing a diaphragm, characterized in that: include: S1: performing a first mixing process on a foaming material, a polymer material and a solvent to obtain a first mixed liquid; S2: adding a pore-forming agent to the first mixed solution for a second mixing treatment to obtain a second mixed solution; S3: performing a casting process, an immersion process and a drying process on the second mixed liquid to obtain a diaphragm.

5. The method according to claim 4, characterized in that The pore-forming agent is water and / or ethanol; Optionally, the mass of the pore former is 0.5wt.% to 5wt.% of the mass of the first mixed solution; Optionally, the pouring treatment and the immersion treatment are performed by pouring the second mixed liquid on the substrate to form a liquid film, and then immersing the substrate in water.

6. A method for preparing a diaphragm, characterized in that: include: A1: performing a first mixing process on a foaming material, a polymer material and a solvent to obtain a first mixed liquid; A2: The first mixed solution is subjected to electrospinning and drying to obtain a separator.

7. The method according to claim 6, characterized in that The electrospinning treatment is carried out by loading the first mixed solution into an electrospinning syringe. The positive high voltage of the electrospinning treatment is 10-20 kV, the negative high voltage is 0-5 kV, the injection speed is 0.2-5 mL / h, the drum speed is 20-100 rpm, and the distance between the positive and negative electrodes is 10-20 cm.

8. The method according to any one of claims 4 or 6, characterized in that: The foaming material is one or a mixture of azo organic matter, hydrazide organic matter, urea derivative or azide compound; Optionally, the polymer material is one or a mixture of polyethylene, polypropylene, polyvinylidene fluoride, polyacrylic acid, polyacrylonitrile, polymethyl methacrylate, polyethylene oxide, polyimide, polyvinylidene fluoride-hexafluoropropylene, polyisophthalamide cellulose or chitosan; Optionally, the solvent is one or a mixture of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, acetone, butanone, tetrahydrofuran, acetonitrile, and methanol; Optionally, the mass fraction of the foaming material is 1wt.%-10wt.%, and the mass fraction of the polymer material is 90wt.%-99wt.%; Optionally, the mass fraction of the foaming material and the polymer material in the first mixed solution is 1wt.% to 15wt.%; Optionally, the drying temperature is 60-80°C.

9. A diaphragm, characterized in that: The diaphragm is prepared by the method according to any one of claims 4 to 8.

10. A battery, characterized in that: The battery comprises the separator according to any one of claims 1 to 3 or the separator according to claim 9.

Citation Information

Patent Citations

  • Polypropylene composite diaphragm with low-temperature thermal hole closing mechanism, preparation method of polypropylene composite diaphragm and lithium ion battery

    CN113078414A

Cited By

  • Diaphragm, preparation method thereof and electric device

    CN122158876A